Supervising in the digital shadows: language, technology, and emotional labor in postgraduate education: A qualitative case study. - Mbanjwa, Sibonelo Thanda (Student’s Journal of Health Research Africa, 2025)
Background Postgraduate supervision is a cornerstone of academic success; yet, it has become increasingly complex in the digital era. In multilingual and resource-constrained contexts such as South Africa, the intersection of language barriers, technological limitations, and emotional labour complicates supervisory relationships. These challenges often lead to miscommunication, psychological strain, and a decline in academic progress. This study explored the lived experiences of postgraduate students, supervisors, and programme coordinators in navigating digital supervision, focusing on identifying challenges and opportunities for improved practice. Methods This qualitative case study was conducted between January and March 2024 at two South African public universities. A purposive sample of 54 participants was selected, comprising 44 postgraduate students (28 master’s, 16 doctoral), 6 academic supervisors, and 4 programme coordinators. Data collection involved 18 semi-structured interviews and two virtual focus groups. Braun and Clarke’s six-phase thematic analysis was applied, with triangulation across participant groups to enhance credibility. Results Participants included 20 males and 34 females, aged 25–52 years (mean = 36 years). Three key themes emerged. First, language barriers hindered effective feedback, as students with limited academic English proficiency struggled to express ideas clearly. Second, emotional labour was reported by both groups: supervisors experienced digital fatigue, while students reported isolation, anxiety, and frustration. Third, digital inequalities such as poor connectivity and low digital literacy exacerbated power imbalances, leaving students hesitant to engage fully with their supervisors. Conclusion Digital supervision, though flexible, intensifies existing challenges related to language, emotional well-being, and technology. Without adequate institutional support, both supervisors and students face heightened stress and reduced academic outcomes. Recommendations Institutions should provide structured writing support, digital supervision training, equitable infrastructure, and wellness systems to strengthen postgraduate supervision in online and hybrid environments.